2015
DOI: 10.1007/s00394-015-0891-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of dietary habits in relation to obesity in Iranian adults

Abstract: Irregular meal pattern and more intra-meal drinking were associated with increased odds of general and abdominal obesity, whereas moderate-to-high intake of fatty foods was related to the decreased odds of central obesity among Iranian adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 30 publications
0
46
1
5
Order By: Relevance
“…The average daily intake of spicy foods was estimated using a validated dietary habit questionnaire [19] by asking the following question: "How frequently do you consume spices (pepper, curry, ginger, cinnamon, and turmeric) during a week?" Subjects could answer this question by selecting one of the following options: never, 1-3, 4-6 and ≥7 times per week.…”
Section: Assessment Of Spicy Food Consumptionmentioning
confidence: 99%
“…The average daily intake of spicy foods was estimated using a validated dietary habit questionnaire [19] by asking the following question: "How frequently do you consume spices (pepper, curry, ginger, cinnamon, and turmeric) during a week?" Subjects could answer this question by selecting one of the following options: never, 1-3, 4-6 and ≥7 times per week.…”
Section: Assessment Of Spicy Food Consumptionmentioning
confidence: 99%
“…Several reports from previous studies have indicated meal nutrient composition especially before dinner may alter circadian regulation [13,27,28]. Also, irregular meal pattern may be associated with increased odds EDS through obesity [16] and cardiometabolic risk factors [29].…”
Section: Discussionmentioning
confidence: 99%
“…We observed an association between a high intake of intra- Another mechanism by which intra-fluid intake and chewing insuffiency elevate the prevalence of EDS may be related to increased risk of obesity [16,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study on 7,958 Iranian adults, irregular meal pattern was also associated with greater odds of obesity. After adjustment for potential confounders, individuals with irregular meal patterns were more likely to have general and abdominal obesity, compared with those who had a regular meal pattern (ate 3 main meals per day) [55]. Numerous studies have established that low meal frequency is associated with higher 24-hour insulin concentrations when compared with high meal frequency.…”
Section: Discussionmentioning
confidence: 99%